Does Service Quality Influence Tax Compliance Behaviour of SMEs? A New Perspective from Ghana - Susuawu, Daniel; Ofori-Boateng, Kenneth; Amoh, John Kwaku (International Journal of Economics and Financial Issues, 2020)
While many factors influence tax compliance behaviour, this study aims to examine the effect of the quality of tax services on the compliance behaviour of small and medium-sized enterprises. The study used the survey to test those theories with the aid of frequency tables, regression and correlation analyses. The study found statistically significant positive effects of reliability, responsiveness, assurance, and empathy on the tax compliance behaviour of SMEs. Secondly, there are varying positive correlations amongst key tax service quality measures. The research has several implications for taxing authorities and policy makers due to its effect on tax revenue generation for economic growth and development. The novelty of this paper lies in its premier attempt to enrich the literature on the tax service quality- tax compliance behaviour nexus with the adoption of Parasuraman et al. (1988)’s service quality indicators. In employing these tax service quality indicators, a better understanding is gained into tax non-compliance behaviour, which emanates from poor service quality. The findings provide some insights to taxing authorities and policy makers in drafting policies to enhance tax compliance by improving, digitising and modernising tax administration for maximum revenue mobilisation to drive economic growth. Keywords: Tax, Service, Quality, Compliance, Ghana, Economic Growth, SMEs JEL Classifications: H2, Q2, Q3 DOI: https://doi.org/10.32479/ijefi.10554